Evolution of the Po–Alpine River System during the Last 45 Ky Inferred from Stratigraphic and Compositional Evidence (Ostiglia, Northern Italy) - Luca Demurtas; Luigi Bruno; Stefano Lugli; Daniela Fontana (Geosciences, 2022)
The stratigraphic and compositional study of three sediment cores recovered close to the Po River near Ostiglia provides clues on changes in fluvial dynamics at the transition from the last glacial to the present interglacial. Upper Pleistocene units are dominated by sands with high content in volcanic lithics, denoting high sediment supply from the south-Alpine fluvio-glacial tributary system. The Early–Mid Holocene unit, peat-rich and barren in fluvial sands, results from low sediment supply and waterlogging, encompassing the maximum marine ingression. The Late Holocene unit, characterized by fluvial-channel sands with lower content in volcanics and relatively abundant metamorphic lithics, records the Po River sedimentation since the Late Bronze Age. Late Holocene sands show a lower content in siliciclastic lithic fragments (supplied mainly by Apennine tributaries) compared to modern Po River sands. This distinctive composition could reflect the diversion of Apennine sediments into a southern Po River branch during the Late Bronze Age and into an Apennine collector flowing south of Ostiglia during Roman times and the Middle Ages. The integrated stratigraphic-compositional methods used in this study permitted to reconstruct the major climate-related changes in sediment dispersal and may be potentially applied to other alluvial and coastal settings.